The Role of School Principal Management in the Implementation of a Point System Toward Changes in Student Discipline and Learning Motivation at SMA Negeri 1 Calang, Aceh Jaya Regency - Maswadi M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Discipline and learning motivation are two key factors that significantly determine the success of the educational process in schools. However, many schools, including SMA Negeri 1 Calang in Aceh Jaya Regency, face problems related to low levels of student discipline and learning enthusiasm. This phenomenon impacts the effectiveness of learning and students' academic achievement. Based on this condition, innovative managerial efforts from school principals are required to design strategies for student character development. One such approach is the implementation of a point system, a structured mechanism in which students receive positive or negative points based on their behavior and achievements. This study aims to examine the role of school principal management in designing and implementing the point system and to analyze its effectiveness in improving student discipline and learning motivation. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The subjects of the study include the school principal, guidance and counseling teachers, homeroom teachers, and students at SMA Negeri 1 Calang. The findings reveal that the school principal plays an active role in the planning, implementation, and evaluation of the point system by involving various school components. The point system proves effective in increasing students' awareness of the importance of discipline and provides psychological encouragement through rewards for positive behavior and achievements. The system also fosters a healthy competitive culture and strengthens students' overall character.